CBX2 enhances the progression and TMZ chemoresistance of glioma via EZH2-mediated epigenetic silencing of PTEN expression - Wang, Jian; Yang, Bo; Wang, Yingzhao; Liu, Shuhan; Ma, Changkai; Piao, Jianmin; Ma, Shiqiang; Yu, Dehai; Wu, Wei (Frontiers in Pharmacology, 2024)
Chromobox (CBX) 2 , a member of the CBX protein family and a crucial component of the polycomb-repressive complex (PRC), exerts significant influence on the epigenetic regulation of tumorigenesis, including glioma. However, the precise role of CBX2 in glioma has remained elusive. In our study, we observed a substantial upregulation of CBX2 expression in glioma, which displayed a strong correlation with pathological grade, chemoresistance, and unfavorable prognosis. Through a series of in vivo and in vitro experiments, we established that heightened CBX2 expression facilitated glioma cell proliferation and bolstered resistance to chemotherapy. Conversely, CBX2 knockdown led to a significant inhibition of glioma cell growth and a reduction in chemoresistance. Notably, our investigation uncovered the underlying mechanism by which CBX2 operates, primarily by inhibiting PTEN transcription and activating the AKT/mTOR signalling pathway. Conversely, silencing CBX2 curtailed cell proliferation and attenuated chemoresistance by impeding the activation of the PTEN/AKT/mTOR signalling pathway. Delving deeper into the molecular intricacies, we discovered that CBX2 can recruit EZH2 and modulate the trimethylation of histone H3 lysine 27 (H3K27me3) levels on the PTEN promoter, effectively suppressing PTEN transcription. Our research unveils a comprehensive understanding of how CBX2 impacts the tumorigenesis, progression, chemoresistance, and prognosis of glioma. Furthermore, it presents CBX2 as a promising therapeutic target for drug development and clinical management of glioma.